Antizyme inhibitor 1: a potential carcinogenic molecule. Issue 2 (February 2017) - Qiu, Shiqiao; Liu, Jing; Xing, Feiyue
Abstract : Polyamines are multivalent and organic cations essential for cellular growth, proliferation, differentiation, and apoptosis. Increased levels of polyamines are closely associated with numerous forms of cancer. An autoregulatory circuit composed of ornithine decarboxylase (ODC), antizyme (AZ) and antizyme inhibitor (AZI) govern the intracellular level of polyamines. Antizyme binds with ODC to inhibit ODC activity and to promote the ubiquitin‐independent degradation of ODC. Antizyme inhibitor binds to AZ with a higher affinity than ODC. Consequently, ODC is released from the ODC–AZ complex to rescue its activity. Antizyme inhibitor increases the ODC activity to accelerate the formation of intracellular polyamines, triggering gastric and breast carcinogenesis as well as hepatocellular carcinoma and esophageal squamous cell carcinoma development. Antizyme inhibitor 1 (AZIN1), a primary member of the AZI family, has aroused more attention because of its contribution to cancer. Even though its conformation is changed by adenosine‐to‐inosine (A→I) RNA editing, it plays an important role in tumorigenesis through regulating intracellular polyamines. Encouragingly, AZIN1 has been revealed to have an additional function outside the polyamine pathway so as to bypass the deficiency of targeting the polyamine biosynthetic pathway, promising to become a critical target for cancer therapy. Here, we review the latest research advances into AZIN1 and its potential contribution to carcinogenesis. Abstract : Polyamines are multivalent, organic cations essential for cellular growth, proliferation, differentiation and apoptosis. Antizyme inhibitor 1 is proved to play an important role in tumorigenesis through regulating intracellular polyamine levels, promising to become a critical target for anti‐cancer therapy. we congregate the latest advances on the AZIN1 molecule and discuss its potential contribution to carcinogenesis.